2022
DOI: 10.1590/1806-9282.20220941
|View full text |Cite
|
Sign up to set email alerts
|

Does pulmonary hypertension affect early-term outcomes of off-pump coronary artery bypass surgery?

Abstract: OBJECTIVE: This study aimed to investigate the effect of preoperative pulmonary hypertension (PHT) on postoperative early mortality and morbidity in patients undergoing off-pump coronary artery bypass grafting (CABG). METHODS: A total of 1107 patients undergoing elective first-time off-pump CABG between January 2011 and April 2022 were included in this retrospective observational cohort study. The patients were categorized into two groups according to their preoperative systolic pulmonary artery pressure (SPAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In this study, in which pulmonary hypertension was investigated as a risk factor, we think that the frequency of COPD is a very important parameter. In this study, the frequency of COPD was found to be 22.1% in the PHT group and 7.4% in the non-PHT group, with a p-value of 0.019 1 . Considering the number of patients in the patient groups, we think that the p-value may be inaccurate with the current rates.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…In this study, in which pulmonary hypertension was investigated as a risk factor, we think that the frequency of COPD is a very important parameter. In this study, the frequency of COPD was found to be 22.1% in the PHT group and 7.4% in the non-PHT group, with a p-value of 0.019 1 . Considering the number of patients in the patient groups, we think that the p-value may be inaccurate with the current rates.…”
mentioning
confidence: 54%
“…The PHT group (n=104) consisted of patients with an SPAP value >30 mmHg, while the non-PHT group (n=1003) consisted of patients with an SPAP value ≤30 mmHg. The authors concluded that both patient groups had similar postoperative outcomes 1 . Could this be due to the large number of patients with an SPAP value between 30 and 50 mmHg?…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study reported no difference in early-term outcomes after OPCAB surgery between pulmonary hypertension and non-hypertension groups [ 36 ]. However, Table 2 suggests that preoperative NYHA, beta blocker use, and emergency surgery are important confounding factors in the development of postoperative MACE.…”
Section: Discussionmentioning
confidence: 99%